2016
DOI: 10.1016/j.trpro.2016.06.063
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Automated Vehicle Effects on Driver's Behavior and Traffic Performance

Abstract: Advanced Driver Assistance Systems (ADAS) offer the possibility of helping drivers to fulfill their driving tasks. Automated vehicles (AV) are capable of communicating with surrounding vehicles (V2V) and infrastructure (V2I) in order to collect and provide essential information about the driving environment. Studies have proved that automated driving have the potential to decrease traffic congestion by reducing the time headway (THW), enhancing the traffic capacity and improving the safety margins in car follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
106
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(112 citation statements)
references
References 8 publications
5
106
0
1
Order By: Relevance
“…This can reduce or optimize gaps between vehicles on the road and results in a smooth and safe traffic flow. It was found that a small percentage of vehicles equipped with these technologies results in a drastic reduction in traffic congestion, and thus increases traffic stability and road capacity (Kesting et al 2007, Ioannou and Chien 1993, Aria et al 2016, Tientrakool et al 2011, Arnaout and Bowling 2011. This is consistent with the findings of the report Co-published by World Economic Forum and Boston consulting group in 2018.…”
Section: Benefits Of Autonomous Vehiclessupporting
confidence: 84%
See 1 more Smart Citation
“…This can reduce or optimize gaps between vehicles on the road and results in a smooth and safe traffic flow. It was found that a small percentage of vehicles equipped with these technologies results in a drastic reduction in traffic congestion, and thus increases traffic stability and road capacity (Kesting et al 2007, Ioannou and Chien 1993, Aria et al 2016, Tientrakool et al 2011, Arnaout and Bowling 2011. This is consistent with the findings of the report Co-published by World Economic Forum and Boston consulting group in 2018.…”
Section: Benefits Of Autonomous Vehiclessupporting
confidence: 84%
“…In total 18 scenarios were simulated. Each scenario was simulated for 5 runs using different random seed numbers, then the trimmed average of the three middle values for each scenario were considered as the average result (Aria et al 2016, Ngan et al 2004.…”
Section: Methodsmentioning
confidence: 99%
“…Another very important setting parameter-in order to enhance the simulation-was the insertion of Desired Speed Decision at 30 km/h, placed 15 m before the roundabout along each arm. The Autonomous Vehicles (AVs) calibration was done by using and adjusting VISSIM parameter set for the "Driving Behaviour Parameter Set\Wiedemann 99\Following" according to the assumptions made by [9,16,17].…”
Section: Microsimulation Methodologymentioning
confidence: 99%
“…Furthermore, the optimal setting obtained by 10 calibration parameters for AVs, all labeled with a "CC" prefix-each of the parameters controls a unique aspect of the car following model as illustrated in Figure 6 was [17,18] For the above reported roundabout schemes, Omisalj and Malinska, four different traffic configurations (TC) were considered:…”
Section: Microsimulation Methodologymentioning
confidence: 99%
See 1 more Smart Citation